No sure victory measuring U.S. Army effectiveness and progress in the Vietnam War - Daddis, Gregory A., 1967- (New York ; Oxford : Oxford University Press, 2011)
Filled with incisive analysis and rich historical detail, this book is a resource for Vietnam War historians and current military professionals alike. The text provides a take on the well-worn issue of determining the root cause of US military failure in Vietnam.
Description based on print version record.
Includes bibliographical references and index.
Keywords: United States. -- Army -- Evaluation; United States. -- Army -- History -- Vietnam War, 1961-1975.; Vietnam War, 1961-1975 -- United States